1996
DOI: 10.1021/js9503791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cyclosporin A Absorption from LCT and MCT Solutions following Intrajejunal Administration in Conscious Dogs

Abstract: Absorption from the intestine of cyclosporin A (CsA), dissolved in either a medium-chain (MCT) or a long-chain triglyceride (LCT) solution, was investigated in a chronic dog model. Following intrajejunal administration of 20 mg of CsA/kg of body weight, absorption, judged by the portalvenous appearance of CsA, was determined by measuring whole blood CsA concentrations in the portalvenous and arterial blood and the portalvenous flow. Appearance of CsA from LCT commenced earlier and attained significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…On first examination, the data appear contradictory and some reveal better performance for MCT 21,22 whilst others suggest a preference for LCT 13,[23][24][25] (see Ref. 14 for a review). However, closer examination reveals that the two studies performed using either fasted healthy humans or dogs 13,24,25 showed, in agreement with our results, higher drug exposure after administration of poorly water-soluble compounds in LCT solution formulations. All the other studies (including all those where MCT was shown to be most preferable) were conducted in rats.…”
Section: Lipid Solution Formulations (Study 1)mentioning
confidence: 99%
“…On first examination, the data appear contradictory and some reveal better performance for MCT 21,22 whilst others suggest a preference for LCT 13,[23][24][25] (see Ref. 14 for a review). However, closer examination reveals that the two studies performed using either fasted healthy humans or dogs 13,24,25 showed, in agreement with our results, higher drug exposure after administration of poorly water-soluble compounds in LCT solution formulations. All the other studies (including all those where MCT was shown to be most preferable) were conducted in rats.…”
Section: Lipid Solution Formulations (Study 1)mentioning
confidence: 99%
“…Cyclosporin (CY) is a cyclic undecapeptide with potent immunosuppressive activity, which is lipophilic (log P 2.92) and poorly water soluble. Behrens et al subsequently proposed that the improved intestinal absorption of CY from LCT vehicles was a function of the improved capacity of the products of LCT digestion to intercalate into intestinal mixed micelles (62). Subsequent studies confirmed these data and showed that the absorption of cyclosporin was significantly improved after administration in a lipid vehicle made up of glycerides of long-chain fatty acids compared with MCT (60).…”
Section: Bioavailability Enhancement By Means Of Physicochemical Mechmentioning
confidence: 99%
“…Кишечная лимфатическая система -уникальный высокоёмкий путь транспорта для некоторых липофильных лекарств через клетку, особенно при одновременном введении с липидами [22]. Транспорт в лимфу показан для многих высоко липофильных лекарств и ксенобиотиков: производных тестостерона, пробукола, циклоспорина, ретиноидов, ликопина и др [22,40]. Скорость такого транспорта невелика, так как скорость движения лимфы ~ в 500 раз ниже скорости кровотока в воротной вене.…”
Section: поступление липофильных лекарств через лимфатический транспортunclassified